Agricultural price in India - "Gulati, Ashok" (New Delhi, 1987)
The most pertinent question in Indian agricultural price policy, for policy makers and farmers alike, relates to the fixation of procurement price for the relevant commodity. This book is essentially an econometric apprach to answer this pivotal question in a scientific way. An attempt has been made to equip the policy maker with an econometric model, which would enable him to have an ex-ante information regarding the plausible effects of his decision to fix the procurement price on the relevant variables of the food grain sector.
Keywords: Agricultural prices India